To solve the expression \(-3 \times \frac{1}{3} \times \left(-\frac{4}{5}\right) \div \frac{2}{5}\), we can follow these steps:
-
Multiply the first two numbers: \[ -3 \times \frac{1}{3} = -1 \]
-
Now multiply by \(-\frac{4}{5}\): \[ -1 \times \left(-\frac{4}{5}\right) = \frac{4}{5} \]
-
Now divide by \(\frac{2}{5}\): To divide by a fraction, we can multiply by its reciprocal: \[ \frac{4}{5} \div \frac{2}{5} = \frac{4}{5} \times \frac{5}{2} \]
-
Multiply the fractions: \[ \frac{4 \times 5}{5 \times 2} = \frac{20}{10} = 2 \]
So the final answer is: \[ \boxed{2} \]